Determinan Kepuasan Masyarakat: Peran Kualitas Pelayanan pada Unit Pelayanan SKCK Polres Karanganyar - Wahyono Santoso; Didik Setyawan; Yulianto Yulianto (Jurnal Bisnis dan Kewirausahaan, 2024)
Abstract This study aims to examine the effect of service quality built on the dimensions of Tangibles, Reliability, Responsiveness, Assurance and Empathy on Customer Satisfaction at the Karanganyar Station Police SKCK service unit. The research data was obtained through a questionnaire distributed to SKCK applicants at the Karanganyar Police Station SKCK Service Unit. Sampling using probability sampling method with the number of respondents as many as 100 people. Hypothesis testing with SPSS application and multiple linear regression analysis. The results of the study show that partially the dimensions of Tangibles, Reliability and Assurance have a significant effect on customer satisfaction, while the dimensions of responsiveness and empathy do not significantly affect customer satisfaction.